Experiments and Demonstrations in Physics : Bar-Ilan Physics Laboratory. (Bar-Ilan Physics Laboratory Ser., 2006)
This is the inaugural volume of a new book series entitled "The Road to Scientific Success: Inspiring Life Stories of Prominent Researchers". Authoritative scientists such as Nobel Prize laureates Douglas D Osheroff and Herbert A Hauptman and US National Medal of Science recipients Paul Ching-Wu Chu and Eli Ruckenstein describe their life experiences in relation to how success was attained, how their careers were developed, how their research was steered, how priorities were set, and how difficulties were faced. These keys to success serve as a useful guide for anyone who is looking for advice on how to direct their career and conduct scientific research that will make an impact. The focus on the road to success (rather than scientific findings) and on personal experience aims to inspire and encourage readers to achieve greater success themselves. The objectives of this book series are: to motivate young people to pursue their vocations with rigor, perseverance and direction; to inspire students to pursue science or engineering; to enhance the scientific knowledge of students, including those that do not major in science or engineering; to help parents and teachers prepare the next generation of scientists or engineers; to increase the awareness of the general public to the advances of science; to provide a record of the history of science.